Local inflammation at the salmon louse (Lepeophtheirus salmonis) attachment site contributes to copepodid rejection in coho salmon (Oncorhynchus kisutch) - Lene Sveen; Mark D. Fast; Torstein Tengs; Rachel A. Kline; Judit Aguilar Marti; Dominic Kurian; Gerrit Timmerhaus; Marianne Vaadal; Ross D. Houston; James E. Bron; Sean J. Monaghan; Haitham H. Mohammed; et al. (Cell and Tissue Research, 2025)
The study investigates the susceptibility of Atlantic salmon ( Salmo salar ) and Pacific salmon species (pink salmon, Oncorhynchus gorbuscha ; coho salmon, Oncorhynchus kisutch ; and chum salmon, Oncorhynchus keta ) to the parasitic salmon lice ( Lepeophtheirus salmonis ). The research had two main objectives: to characterize the morphology of the scaly skin in four salmonid species and to compare the cellular response at the louse attachment site in coho salmon and Atlantic salmon. Three consecutive challenge trials were conducted, with successful louse infestation only achieved across all four species in the third trial using mild anesthesia with tricaine methanesulfonate. Skin and fin samples were collected at 12, 24, 36, 48, 60, and 168 h post-infestation (hpi) for histological, proteomic, and spatial transcriptomic analyses. Results showed that chum salmon had significantly higher mucous cell coverage (30–40%) in the epithelium of scaly skin compared to Atlantic salmon (10%). At the louse attachment site in coho salmon, there was a greater influx of inflammatory cells at 36–48 hpi compared to Atlantic salmon. Proteomic analysis at 12 hpi and 36 hpi in coho salmon showed upregulation of neutrophil degranulation and formyl-methionyl-leucyl-phenylalanine signaling. Additionally, spatial transcriptomics at the attachment site showed local upregulation of inflammatory gene markers. These findings suggest that coho salmon mount a rapid and large-scale inflammatory response driven by neutrophils to louse attachment within the first 48 hpi. Overall, the study emphasizes the significance of local changes at the host-parasite interface for resistance mechanisms against salmon lice.